2023
DOI: 10.1186/s12912-023-01259-z
|View full text |Cite
|
Sign up to set email alerts
|

Association of pain management and positive expectations with psychological distress and spiritual well‑being among terminally ill cancer patients admitted to a palliative care unit

Abstract: Background Although palliation of psycho-spiritual distress is of great importance in terminally ill cancer patients, there is a little information about screening patients who benefit from palliative care and identifying the cancer care targets. This study explored the relationship of pain management and positive expectations with depression, anxiety and spiritual well-being (SWB) in terminal cancer patients admitted to a palliative care unit. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Given the multidimensional nature, pain not only has a biological basis but also affects and is affected by psychosocial factors, 1–4 resulting in great difficulty in adequate management of cancer pain. Pharmacological method around pain control is of particularly high priority in Chinese palliative settings, 11 12 which may underestimate psychosocial issues in pain management.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the multidimensional nature, pain not only has a biological basis but also affects and is affected by psychosocial factors, 1–4 resulting in great difficulty in adequate management of cancer pain. Pharmacological method around pain control is of particularly high priority in Chinese palliative settings, 11 12 which may underestimate psychosocial issues in pain management.…”
Section: Discussionmentioning
confidence: 99%
“…This was a secondary analysis of prospective studies conducted at the Shengjing Hospital of China Medical University between July 2019 and October 2020. 11 12 A consecutive sample of 147 patients were recruited at the hospice ward. Eligible patients were ≥18 years who had incurable cancer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the relationship between spirituality and pain-related catastrophizing has not yet been explored among people with cancer, one recent study reported a significant relationship between faith and positive expectations (i.e., optimism and general self-efficacy) among people with cancer [ 45 ]. Given that pain-related catastrophizing includes components of magnification, helplessness, and expectation of negative outcomes [ 33 ], interventions focused on enhancing faith, optimism, and self-efficacy could improve pain-related catastrophizing.…”
Section: Discussionmentioning
confidence: 99%
“…Though spirituality can effectively reduce cancer pain [ 2 ], research is needed to clarify which participant characteristics, contexts, and/or types of pain might create conditions for spirituality-centered interventions to be optimized. Interestingly, higher levels of pain are associated with greater spiritual distress [ 35 ], and effective pain management may improve spiritual well-being and psychosocial outcomes among people with cancer [ 45 ], opening possibilities of spirituality and pain existing together in a more complex, reciprocal relationship. Based on these findings, our adapted theoretical framework [ 25 ] may be well suited to additional modification to explore this possibility.…”
Section: Discussionmentioning
confidence: 99%